The Role of E-CRM in Enhancing Organizations Performance - A Case Study on Algerian Telecommunications Company in Tebessa - - Bakhouche, Madiha (Jordan Journal of Business Administration, 2020)
The purpose of this study was to investigate the role of electronic customer relationship management (E-CRM) in enhancing organizations’ performance according to the opinions of employees working at Algerian Telecommunications Company. The researcher used the analytical descriptive approach. The theoretical information was collected from the library sources and the data was collected through a questionnaire distributed to the study population, which was composed of all the company employees. The study found that the respondents’ opinions about E-CRM axis were at the level “agree” on Likert scale. There is also a focus on profitability and loyalty in performance. The results indicate that there is a statistically significant impact of E-CRM on Algerian telecommunications company performance. The electronic customer relationship management explains 35.2%, 31.4% and 25.7% of the change in performance, profitability and loyalty, respectively. The study recommended the increasing of customers’ awareness of the importance of electronic management in their dealings with the organization, along with the training of employees on new expert systems and modern technologies.